Identification of immunogenic and cross-reactive chikungunya virus epitopes for CD4+ T cells in chronic chikungunya disease - Rimjhim Agarwal; Calvin Ha; Fernanda H. Côrtes; Yeji Lee; Amparo Martínez-Pérez; Rosa Isela Gálvez; Izabella N. Castillo; Elizabeth J. Phillips; Simon A. Mallal; Angel Balmaseda; Eva Harris; Claudia M. Romero-Vivas; et al. (Nature Communications)
Abstract Chikungunya virus (CHIKV), a mosquito-borne alphavirus, causes acute febrile illness that can progress into chronic arthritis-like disease (CHIKVD) in humans. CD4+ T cells have important functions in CHIKV infection, yet the CHIKV target proteins for these CD4 + T cells are poorly characterized. Here, by stimulating PBMCs collected from individuals with chronic CHIKVD with peptides spanning the entire CHIKV proteome, we provide a comprehensive landscape of CHIKV CD4+ T cell epitopes. We identify three immunodominant regions and associated core motifs in CHIKV E1, nsP1 and CP proteins. In addition, by in silico assessment of the sequence conservation of CHIKV proteome with closely related alphaviruses, we define CHIKV epitopes conserved across arthritogenic and encephalitic viruses. Overall, our work describes CD4+ T cell targets of CHIKV in humans, thereby assisting in studying the functions of CD4+ T cells in CHIKV pathogenesis and vaccine design.